2023
DOI: 10.3390/jcm12041303
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Imaging Biomarkers in Diabetic Macular Edema Eyes Treated with Intravitreal Dexamethasone Implant

Abstract: Background: The aim was to evaluate predictive value of baseline optical coherence tomography (OCT) and OCT angiography (OCTA) parameters in diabetic macular edema (DME) treated with dexamethasone implant (DEXi). Methods: OCT and OCTA parameters were collected: central macular thickness (CMT), vitreomacular abnormalities (VMIAs), intraretinal and subretinal fluid (mixed DME pattern), hyper-reflective foci (HRF), microaneurysms (MAs) reflectivity, ellipsoid zone disruption, suspended scattering particles in mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Costanzo et al investigated the predictive role of baseline OCT and OCTA parameters in DME eyes treated with a dexamethasone implant (DEXi). These authors found that statistical models based on the combination of baseline OCT and OCTA parameters may help in the identification of DME eyes responding to a DEXi in the treatment-naïve group [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costanzo et al investigated the predictive role of baseline OCT and OCTA parameters in DME eyes treated with a dexamethasone implant (DEXi). These authors found that statistical models based on the combination of baseline OCT and OCTA parameters may help in the identification of DME eyes responding to a DEXi in the treatment-naïve group [ 38 ].…”
Section: Discussionmentioning
confidence: 99%